Hipomineralização molar incisivo: origem e associações com doença periodontal e cárie no adolescente: Coorte RPS, Brasil - FRANCO, Marcela Mayana Pereira (2023)
Molar Incisor Hypomineralization (IMH) is an enamel defect that occurs in first permanent molars with or without incisor involvement. The enamel has demarcated opacities that vary between white, yellow and brown. The etiology remains unknown, but it is known that environmental stressors can interact with genetic factors and result in enamel defects. If, on the one hand, MIH is the outcome that highlights gestational and perinatal weaknesses; on the other, it is exposure to caries disease. This is due to the reduction in brushing resulting from hypersensitivity, the susceptibility to fracture which also favors the accumulation of biofilm and the greater porosity of the enamel which favors the infiltration of bacteria. It is known, however, that, consistently, indicators of caries and periodontal disease are correlated with each other, having risk factors in common, such as biofilm accumulation and sugar consumption, which leads us to the hypothesis that in addition to caries, MIH may also be an exposure capable of influencing periodontal disease, both due to its relationship with caries and by favoring the colonization of proteolytic bacteria, since the hypomineralized surface provides a protein substrate, which would facilitate the adhesion and growth of these bacteria. bacteria that are characteristic of the dysbiotic biofilm that triggers periodontal disease. In this way, the products of this thesis address MIH from two perspectives: at the beginning of the life cycle as an outcome of pre- and peri-natal factors and as exposure to oral diseases, periodontal disease and caries. Chapter I of this thesis was Pre- and perinatal stressors associated with Incisor Molar Hypomineralization: Birth cohort, Brazil. This study analyzed exposures in the prenatal and perinatal periods with the occurrence of Incisor Molar Hypomineralization. This is a prospective cohort study RPS, São Luís, Brazil. At the time of birth (baseline), data from the prenatal period (maternal age, number of prenatal consultations, smoking during pregnancy, BMI, previous abortion and gestational hypertension) and perinatal data (type of birth, gestational age) were collected), birth weight, breastfeeding in the first hour of life and ICU admission). The stage of interest was MIH measured in the follow-up of adolescents at 18-19 (n=590), through the Gahin draw. A theoretical model was constructed to analyze the paths in the associations between variations in the prenatal and perinatal periods with MIH, considering the socioeconomic situation as a more distal determinant, through Structural Equation Modeling (SEM). The stage of interest was HMI defined according to Ghanim Model I and a sensitivity analysis was performed where with teeth with demarcated opacities in index teeth independent of molar involvement, Model II. MIH was observed in 15.25% (n=90), and marked opacities in index teeth were observed in 22.8% of adolescents (n=135). In Model I, no stressor explained MIH, however, high Standardized Coefficients (PC) for low birth weight (SC=0.223, p=0.147), lower gestational age (SC=0.351; p=0.254), and ICU admission ( SC=0.447, p=0.254). In model II, Higher maternal age (SC=148; p<0.05) and not receiving prenatal care (SC=405, p<0.03) explained the model. Chapter II of this thesis was entitled: Molar Incisor Hypomineralization and Initial Perodontitis in adolescents: Population- based study, with the objective of: Investigating the association between Incisor Molar Hypomineralization and Periodontitis in adolescents. Cross-sectional study nested within a Cohort (RPS Cohort Consortium) in adolescents aged 18 and 19 (n=2515). The exams were carried out in a dental office to evaluate the presence of MIH (Ganhin criterion) and periodontal examination, where the parameters Visible Plaque Index (IPV), Bleeding on Probing (SS), Clinical Probing Depth (PCS) and Clinical Insertion Level (NIC). A theoretical model was constructed to analyze the association between MIH (exposure) and Early Periodontitis, a latent variable estimated by the common variance shared between bleeding on probing, Probing Depth ≥ 4 mm and Clinical Attachment Level ≥ 3 mm. As a sensitivity analysis, Periodontitis was evaluated according to the classification of Page & Eke and the Center for Disease Control and Prevention (CDC) and the American Academy of Periodontology (AAP). Structural equation modeling was performed to test the proposed model. As more distal variables influencing the entire model, socioeconomic status and sex were considered. The Visible Plaque Index was the variable used as a mediator in the association. HMI explained early periodontitis by a direct path (standardized coefficient [SC] = 0.152, p=0.000) and by an indirect path via biofilm (SC= 0.040 P= 0.000). Consistency analyzes did not demonstrate a significant effect. Our results indicate MIH as a possible exposure associated with the onset of periodontitis and highlight the need for preventive management of patients with MIH. Chapter III of this thesis was entitled: Repercussions of Incisor Molar Hypomineralization on dental caries and DMFT in adolescents: a population-based study with the objective of investigating MIH as an exposure to the increase in caries prevalence and increase in DMFT. Cross-sectional study nested in a cohort with 2515 adolescents aged 18 and 19. Sociodemographic and behavioral data were collected using a standardized questionnaire. The clinical examination was performed to evaluate MIH (according to Ghanim), DMFT and PUFA. The outcome was: untreated caries, DMFT and PUFA. Socioeconomic factors were the adjustment of the analyses, chosen through a directed acyclic graph (GAD). For the exploratory descriptive analysis, the Chi-square test was performed and to test the associations, prevalence ratios were estimated using crude and adjusted Poisson regressions (p<0.05). The prevalence of MIH among adolescents was 15.43% (n=453), untreated dental caries in the sample was 63.35% and the average DMFT was 3.70. Poisson regression showed an association between MIH and the outcomes of untreated caries in the unadjusted (PR=1.25, p<0.001) and adjusted (PR=1.28; <0.001) analysis and with DMFT in the unadjusted analysis (PR =1.01, p<0.001) and adjusted (PR=1.01; p <0.001). Regarding PUFA, the association was not verified neither in the unadjusted analysis (PR=0.95, p<0.282) nor in the adjusted analysis (PR=0.94; <0.272). The presence of MIH is associated with an increased prevalence of dental caries and average DMFT both in the dentition in general and in teeth affected by hypomineralization, indicating a common disease profile among patients with MIH, not only in teeth affected by MIH but in the entire dentition. Chapter IV of this thesis was the product of bibliographic research carried out at the end of the construction of the articles, after realizing the need to disseminate knowledge among clinicians, given the importance of early diagnosis to prevent outcomes in oral health, this is the e-book understanding Incisor Molar Hypomineralization that brought together the evidence on MIH and aims to illustrate for clinicians and dentistry students the concepts, etiology, differential diagnosis and treatment of MIH. It is known that the prevalence of this condition has become more evident. As this is still a recent subject and most accessed by pediatric dentists, it is essential that the information reaches clinicians and students in a didactic and simple way, as all professionals, in the most diverse specialties, must understand the subject.